Pentastrontium trilead nickel dodecaoxide, Sr5Pb3NiO12 - Prior, T; Battle, P (2004)
Single crystals of Sr5Pb3NiO12 have been grown using a flux method and the structure, related to those of Sr 5Pb3MO12 (M = Co or Cu), has been solved by single crystal X-ray methods in space group P62m (a = 10.1356(11), c = 3.5337(3) Å, V = 314.38(6) Å3, Z = 1). The structure of Sr 5Pb3NiO12 contains infinite chains of edge-sharing PbO6 octahedra which are linked together into trigonal pillars by Ni cations which adopt trigonal prismatic coordination. These pillars, which pack in a pseudo hcp array, are separated by strontium cations. There is evidence for some disorder at the prismatic sites.